Pengaruh Soft Sell Advertising Dalam Video Tiktok Terhadap Keputusan Pembelian Produk - I Gede Arsana Wijaya; Merylin Rafael Sitohang; I Gusti Ayu Agung Citra Santika Dewi; Ida Ayu Agung Diah Janawati; Desak Made Kutha Adhya Wagiiswari; Desak Putu Eka Nilakusmawati (Public Service and Governance Journal, 2024)
This study was conducted to determine whether people are interested in buying a product after seeing a product advertisement promoted through the TikTok application and to determine the effectiveness of promoting a product through the TikTok application. In this study, the research method used is descriptive research with a quantitative approach. The data collection method is a questionnaire (google form). Sampling is done by distributing questionnaire links with a target respondent of 200 people who on average use the TikTok application. The research variables in this research include marketing strategies, product purchasing power, and interest in buying products after seeing advertisements aired on the TikTok application. The results showed that TikTok application users consider product promotions carried out through the TikTok application to be more effective than product promotions in other applications.